1987
DOI: 10.1161/01.res.61.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor effects on bovine pulmonary artery endothelial cells.

Abstract: Endothelial cells (ECs) were isolated from bovine pulmonary artery and maintained in long-term culture. On reaching confluency, ECs formed a characteristic "cobblestone" monolayer. One hour after addition of 1 nM platelet-activating factor (PAF) to the growth medium, ECs underwent dramatic changes in shape from their normal polygonal morphology to more elongated spindle-shaped forms. More pronounced effects were evident in the presence of 0.1 nM phorbol-12-myristate-13-acetate (PMA), a potent activator of C ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…PMA treatment of Verge-expressing RBE4 cells leads to a rapid and transient remodeling of the actin cytoskeleton and the formation of paracellular gaps PMA-induced increases in endothelial cell permeability are often associated with changes in cell shape, reorganization of the cytoskeleton, and the formation of paracellular gaps (Antonov et al, 1986;Grigorian and Ryan, 1987;Lynch et al, 1990;Garcia et al, 1992). As noted, control and Verge-expressing RBE4 cell lines form similar monolayers, and staining of nuclei confirm their cell density to be approximately equal (Fig.…”
Section: Stable Verge-expressing Rbe4 Cells Show Increased Sensitivitsupporting
confidence: 61%
“…PMA treatment of Verge-expressing RBE4 cells leads to a rapid and transient remodeling of the actin cytoskeleton and the formation of paracellular gaps PMA-induced increases in endothelial cell permeability are often associated with changes in cell shape, reorganization of the cytoskeleton, and the formation of paracellular gaps (Antonov et al, 1986;Grigorian and Ryan, 1987;Lynch et al, 1990;Garcia et al, 1992). As noted, control and Verge-expressing RBE4 cell lines form similar monolayers, and staining of nuclei confirm their cell density to be approximately equal (Fig.…”
Section: Stable Verge-expressing Rbe4 Cells Show Increased Sensitivitsupporting
confidence: 61%
“…Endothelial cells bind PAF, resulting in increased intracellular calcium, inositol phosphate production, and protein kinase C activity. [31][32][33] PAF synthesis by endothelial cells is elicited by a variety of inflammatory mediators including PAF itself, thrombin, and interleukin-1. 34,35 The effect of PAF on the recruitment and activation of circulating inflammatory cells is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have revealed that PAF can be released from other cell types including platelets (Chignard et al, 1980), neutrophils (Lynch et al, 1979;Betz & Henson, 1980), monocytes and macrophages (Arnoux et al, 1980) and endothelial cells (Camussi et al, 1983b). In addition to its effects on platelets, PAF has been shown to be a potent stimulator of other target cells including neutrophils (Goetzl et al, 1980;O'Flaherty et al, 1981), vascular endothelial cells (Handley et al, 1984;Bussolino et al, 1987;Grigorian & Ryan, 1987), vascular smooth muscle cells and bronchial smooth muscle cells (Findlay et al, 1981;Camussi et al, 1983a;Stimler & O'Flaherty, 1983; Baranes et al, 1986).…”
Section: Introductionmentioning
confidence: 99%